Idiopathic acute eosinophilic pneumonia in a 14-month-old girl - Ha Neul Park; Bo Hyun Chung; Jung Eun Pyun; Kwang Chul Lee; Ji Tae Choung; Choon Hak Lim; Young Yoo (Korean Pediatric Society, 2013)
Idiopathic acute eosinophilic pneumonia (IAEP), characterized by acute febrile respiratory failure associated with diffuse radiographic infiltrates and pulmonary eosinophilia, is rarely reported in children. Diagnosis is based on an association of characteristic features including acute respiratory failure with fever, bilateral infiltrates on the chest X-ray, severe hypoxemia and bronchoalveolar lavage fluid >25% eosinophils or a predominant eosinophilic infiltrate in lung biopsies in the absence of any identifiable etiology. We present a 14-month-old girl who was admitted to our pediatric intensive care unit because of acute respiratory distress. She had a fever, dry cough, and progressive dyspnea for 1 day. Chest X-ray showed multifocal consolidations, increased interstitial markings, parenchymal emphysema and pneumothorax. IAEP was confirmed by marked pulmonary infiltrates of eosinophils in the lung biopsy specimen. Most known causes of acute eosinophilic pneumonia, such as exposure to causative drugs, toxins, second-hand smoking and infections were excluded. Her symptoms were resolved quickly after corticosteroid therapy.